أثر التسويق القائم على البيانات على جذب العملاء الجدد لمصرف شمال أفريقيا - فرع صبراته (Al-Farooq Journal of Sciences, 2025)
This research aims to study data-driven marketing at the North Africa Bank - Sabratha branch, examining customer awareness of this concept and its impact on their banking decisions. It also evaluates their use of personalized offers based on data analysis and the effectiveness of digital marketing campaigns in attracting customers. A descriptive analytical approach was used in this study, and data was collected through a questionnaire distributed to a random sample of 63 customers. The results showed that 85.7% of customers had heard of data-driven marketing, indicating a good prevalence of this concept among customers. It also showed that 95.2% of customers use the bank's services regularly, reflecting a high level of trust and reliability in the bank. The results also showed that 81.0% of customers believe that data-driven marketing directly impacts their financial decisions. Meanwhile, 66.7% of customers benefited from personalized offers based on data, highlighting the effectiveness of these campaigns. 71.4% of customers also reported that data-driven marketing contributed to attracting new customers to the bank. 57.1% of customers believe that the bank respects their data privacy, indicating a need to improve data protection policies and build greater trust. The results also showed that 66.7% of customers believe that digital marketing campaigns are effective. Based on these findings, several recommendations were made, such as organizing workshops to introduce customers to the concept of data-driven marketing, using artificial intelligence tools to personalize offers and services, improving data protection, and developing digital applications to support marketing campaigns. Additionally, it was suggested that similar studies be conducted in other branches and that the research be expanded to include the relationship between data-driven marketing and customer loyalty, as well as the impact of trust in the bank on the effectiveness of marketing campaigns.
Keywords: Marketing impact, data, new customers, North Africa Bank, Sabratha branch